Defense Budget Gaps and Legal Implications of Alternative Financing in Indonesia: A Legal Reform Perspective - Aris Marsudiyanto; Athor Subroto; Bambang Permadi Soemantri Brodjonegoro; A. Hanief Saha Ghafur (Journal of Law and Legal Reform, 2024)
This paper examines the critical defense budget gap in Indonesia, which has become a pressing issue over the past decade. With global challenges, particularly the escalating wars in the Middle East, Indonesia faces growing security concerns that necessitate a stronger defense program. However, the country’s defense budget allocation, ranging from 0.5 to 0.9 percent of GDP, remains insufficient to meet the required defense expenditures. Using the Autoregressive Integrated Moving Average (ARIMA) approach, we predict future budget availability and compare it with the projected defense needs, revealing a significant gap. To address this, the paper explores alternative financing mechanisms, such as optimizing military assets, enhancing the defense industry, leveraging Public-Private Partnerships (PPP), and integrating these strategies. The urgency of addressing this funding shortfall is heightened by Indonesia’s need for robust defense capabilities in an increasingly unstable geopolitical environment. This study’s novelty lies in analyzing the legal implications of these alternative financing options, an area that has received limited attention in defense policy discourse. It critically examines the legal challenges posed by these financing mechanisms, particularly in relation to Indonesia’s existing laws, including Law No. 17 of 2003 on State Finances, Law No. 3 of 2002 on National Defense, and various regulations governing defense industry and national security. The paper’s contribution lies in offering a comprehensive legal analysis of alternative financing in Indonesia’s defense sector, proposing necessary legal reforms to facilitate these strategies. By providing policy recommendations, this study aims to inform lawmakers, defense planners, and legal scholars about the complexities and potential solutions to closing Indonesia’s defense budget gap while ensuring compliance with national legal frameworks.